Comparison of 0.5% Bupivacaine vs 0.5% Bupivacaine with Dexamethasone in USG Guided Axillary Brachial Plexus Block - A Prospective, Randomised, Double Blinded Study - G. Venkatesan; T. Padma Rubini (Academia Anesthesiologica International, 2021)
Background: Long-acting local anaesthetic bupivacaine is widely used in brachial plexus blocks. Ultrasound guidance reduces procedure time, speeds up the onset of operation, and increases block success rates without causing neural injuries, both of which improve effectiveness. The addition of dexamethasone to regional anaesthesia with local anaesthetics has given corticosteroids a new dimension in medical practice. The aim isto compare0.5% bupivacaine and 0.5% bupivacaine with dexamethasone in ultrasound-guided axillary brachial plexus block. Subjects and Methods: In this study, 60 patients were divided into 2 groups, Group B (n=27) control group received 18ml of 0.5% Bupivacaine with 2ml of isotonic sodium chloride solution and Group BD received 18ml of 0.5% Bupivacaine with 2ml (8mg) of dexamethasone. Results: In 60 patients, the onset time of sensory block was earlier in GROUP BD (11.45 2.18) than in GROUP B (13.85 3.76) (P=0.003). Duration of motor block was longer in GROUP BD (581.52 47.97) than in GROUP B (427.04 21.81) (P <0.0001). GROUP BD (808.48 35.98) has a significantly longer duration of analgesia than in GROUP B (627.41 36.54) (P<0.001). Total dose of rescue analgesia was lower in GROUP BD (112.12 33.14) when compared to GROUP B (192.59 47.44) (P<0.0001). Conclusion : To conclude, 0.5% Bupivacaine with 2ml (8mg) of dexamethasone combination effectively provides postoperative analgesia and delays the time for rescue analgesia.